Resveratrol Produces Neurotrophic Effects on Cultured Dopaminergic Neurons through Prompting Astroglial BDNF and GDNF Release. (28th November 2012) - Zhang, Feng; Wang, Yan-Ying; Liu, Hang; Lu, Yuan-Fu; Wu, Qin; Liu, Jie; Shi, Jing-Shan
Abstract : Increasing evidence indicated astroglia-derived neurotrophic factors generation might hold a promising therapy for Parkinson's disease (PD). Resveratrol, naturally present in red wine and grapes with potential benefit for health, is well known to possess a number of pharmacological activities. Besides the antineuroinflammatory properties, we hypothesized the neuroprotective potency of resveratrol is partially due to its additional neurotrophic effects. Here, primary rat midbrain neuron-glia cultures were applied to investigate the neurotrophic effects mediated by resveratrol on dopamine (DA) neurons and further explore the role of neurotrophic factors in its actions. Results showed resveratrol produced neurotrophic effects on cultured DA neurons. Additionally, astroglia-derived neurotrophic factors release was responsible for resveratrol-mediated neurotrophic properties as evidenced by the following observations: (1) resveratrol failed to exert neurotrophic effects on DA neurons in the cultures without astroglia; (2) the astroglia-conditioned medium prepared from astroglia-enriched cultures treated with resveratrol produced neurotrophic effects in neuron-enriched cultures; (3) resveratrol increased neurotrophic factors release in the concentration- and time-dependent manners; (4) resveratrol-mediated neurotrophic effects were suppressed by blocking the action of the neurotrophic factors. Together, resveratrol could produce neurotrophic effects on DA neurons through prompting neurotrophic factors release, and these effects might open new alternative avenues for neurotrophic factor-based therapy targeting PD.